Current Status of Endoscopic Gallbladder Drainage - Joey Ho Yi Chan; Anthony Yuen Bun Teoh (Korean Society of Gastrointestinal Endoscopy, 2018)
The gold standard for treatment of acute cholecystitis is laparoscopic cholecystectomy. However, cholecystectomy is often not suitable for surgically unfit patients who are too frail due to various co-morbidities. As such, several less invasive endoscopic treatment modalities have been developed to control sepsis, either as a definitive treatment or as a temporizing modality until the patient is stable enough to undergo cholecystectomy at a later stage. Recent developments in endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) with endoscopic ultrasound EUS-specific stents having lumen-apposing properties have demonstrated potential as a definitive treatment modality. Furthermore, advanced gallbladder procedures can be performed using the stents as a portal. With similar effectiveness as percutaneous transhepatic cholecystostomy and lower rates of adverse events reported in some studies, EUS-GBD has opened exciting possibilities in becoming the next best alternative in treating acute cholecystitis in surgically unfit patients. The aim of this review article is to provide a summary of the various methods of gallbladder drainage GBD with particular focus on EUS-GBD and the many new prospects it allows.